Bovine milk-derived extracellular vesicles prevent gut inflammation by regulating lipid and amino acid metabolism. Issue 4 (9th February 2023) - Du, Chunmei; Quan, Suyu; Zhao, Yiguang; Nan, Xuemei; Chen, Ruipeng; Tang, Xiangfang; Xiong, Benhai
Abstract : Inflammatory bowel disease (IBD) is a global health problem in which metabolite alteration plays an important pathogenic role. Abstract : Inflammatory bowel disease (IBD) is a global health problem in which metabolite alteration plays an important pathogenic role. Bovine milk-derived extracellular vesicles (mEVs) have been shown to regulate nutrient metabolism in healthy animal models. This study investigated the effect of oral mEVs on metabolite changes in DSS-induced murine colitis. We performed metabolomic profiling on plasma samples and measured the concentrations of lipids and amino acids in both fecal samples and colonic tissues. Plasma metabolome analysis found that mEVs significantly upregulated 148 metabolite levels and downregulated 44 metabolite concentrations (VIP > 1, and p < 0.05). In the fecal samples, mEVs significantly increased the contents of acetate and butyrate and decreased the levels of tridecanoic acid (C13:0), methyl cis -10-pentadecenoate (C15:1) and cis -11-eicosenoic acid (C20:1). Moreover, the concentrations of eicosadienoic acid (C20:2), eicosapentaenoic acid (C20:5), and docosahexaenoic acid (C22:6) were decreased in colonic tissues with mEV supplementation. In addition, compared with the DSS group, mEVs significantly increased the content of l -arginine, decreased the level of l -valine in the fecal samples, and also decreased the levels of l -serine and l -glutamate in the colonic tissues. Collectively, our findings demonstrated that mEVs could recover the metabolic abnormalities caused by inflammation and provided novel insights into mEVs as a potential modulator for metabolites to prevent and treat IBD.